Outcomes and surgical technique of laparoscopic hysterectomy using an articulating laparoscopic instrument: a prospective observational study - Seo, Jun-Hyeong; Kim, Won-Ji; Choi, Chel Hun; Kim, Tae-Joong; Lee, Jeong-Won; Kim, Byeong-Gie; Kato, Kazuyoshi; Lee, Yi-Liang; Chen, Yu-Li; Lee, Yoo-Young (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to evaluate the feasibility of performing laparoscopic hysterectomy using an articulating laparoscopic instrument that provides flexible and ergonomic movements similar to robotic systems and to demonstrate the surgical techniques facilitated by this advanced instrument.MethodsThis prospective observational study was performed at a single institution. We reviewed the electronic medical records of patients who underwent laparoscopic hysterectomy using an articulating laparoscopic instrument between October 2022 and May 2023. The surgeries were performed by two surgeons, both experienced in laparoscopic hysterectomy. Data on patient demographics, clinical outcomes, as well as pathological and postoperative results, were collected prospectively for analysis.ResultsOf the 100 patients enrolled in this prospective observational study utilizing the articulating laparoscopic instrument for gynecologic surgery, 45 underwent hysterectomy with this instrument. All procedures were successfully completed laparoscopically without the need for conversion to laparotomy. Indications for hysterectomy were benign in 55.5% of the patients, borderline in 6.6%, and malignant in 37.7%. Median operative time was 78 min (range, 44–156 min). The median uterine weight was 203.5 g (range, 43–875 g), and the median estimated blood loss was 100 ml (range, 50–300 ml). The median length of hospital stay postoperatively was 2 days (range, 2–4 days). Postoperative complications were observed in six (13.3%) patients, with one developing a vesicovaginal fistula as a delayed complication.ConclusionThe results of this study present the practicality of employing the articulating laparoscopic instrument in laparoscopic hysterectomy, highlighting its efficacy in improving surgical technique. The enhanced maneuverability provided by this instrument allows for precise and efficient operations, demonstrating its value in performing complex surgical procedures.